Normative developmental vs. reverse developmental trends in memory distortion: a framework to investigate the impact of internal and external influences on memory and their relevance to legal decisions - Rosendaul, Brittany J.; Su, I-An; Ceci, Stephen J. (Frontiers in Psychology, 2023)
There are two opposing positions regarding the development of memory: the normative developmental position, and the reverse developmental position. The normative position, which has long been the default presupposition, supports the notion that susceptibility to memory distortion, including false memories, decreases with age. In contrast, the concept of "developmental reversals" supports the notion that susceptibility to memory distortion and false memories increases with age. Each perspective finds support from existing theories as well as from research on endogenous and exogenous sources of influence. In a legal context, having an accurate understanding of the developmental course of false memory can contribute on the one hand to mitigating wrongful convictions and, on the other hand, to appreciating the accuracy of children's statements when warranted. This review aims to integrate the existing literature regarding these seemingly opposite developmental courses and construct a framework outlining the conditions under which we may observe one age trend over the other. This entails an examination of the paradigms that have been invoked to support these competing positions, specifically developmental responses to internal versus external sources of distortion.